Microbiological and biochemical properties of deposols RB 'Kolubara' - Snežana Đorđević; Željko Dželetović; Dragana Stanojević; Zvonko Radan (Zaštita Materijala)
Both microbiological and biochemical properties of 'deposol' at 'Kolubara' Mining Complex, recultivated by plant communities of birch and white pine, were studied. With respect to microbiological investigations, the number of systematic and physiological groups of microorganisms was estimated, while biochemical studies comprised determination of urease and dehydrogenase activity and evaluation of carbon and phosphorus biomass. The 'deposols' at 'Kolubara' Mining Complex differed in their microbiological and biochemical properties, depending on plant communities, formed in order to recultivate these soils. Birch community 'deposols' expressed higher values than white pine community 'deposols' regarding following parameters: total number of microorganisms, number of fungi, number of cellulolytic microorganisms, number of aminoheterotrophs, number of Azotobacter spp., urease and dehydrogenase activity, and both carbon and phosphorus biomass. Conversely, the white pine community 'deposols' expressed higher value of number of ctinomycetes than birch community 'deposols'. Total number of microorganisms, number of fungi, aminoheterotrophs, actinomycetes, and cellulolytic microorganisms, and carbon biomass in 'deposols' was at the level of values of those parameters in natural soils. Parameters concerning both urease and dehydrogenase activity and phosphorus biomass were lower. Number of Azotobacter chroococcum was extremely small at all examined 'deposols', while it was not even detected at certain localities.